Molecular typing of Legionella pneumophila strains isolated from environment in Morocco - Mekkour, M.; Ben driss, E.; Tai, J.; Squinazi, F.; Forey, F.; Jarraud, S.; Cohen, N. (Cellular and Molecular Biology, 2012)
Legionella pneumophila is a common cause of hospital and community-acquired pneumonia, being transmitted by inhalation of aqueous aerosols. Most legionellosis outbreaks are linked to contaminated hot water systems or cooling towers. The aim of this study was to determine the genetic diversity of (n= 55) environmental strains of L. pneumophila recovered from the hot water distribution systems of 16 establishments in seven Moroccan towns during the period 2009–2011. Thirteen chromosomal restriction patterns determined by Pulsed field gel electrophoresis were detected. The strains of L. pneumophila serogroup1 exhibited in 6/13 different PFGE patterns, while the strains of L. pneumophila serogroups 2-14 showed 7/13 PFGE patterns. The PFGE showed the existence of various patterns in Morocco, The pattern -XI- have tree similar profiles with the endemic L. pneumophila Paris’s strain. This technique also allowed to conclude that the same pulsotype was found for many strains isolated from different establishments. Moreover, different pulsolypes were found for strains isolated from the same establishment. These results showed that PFGE analysis is a powerful tool to reveal the clonal nature and genetic differences among L. pneumophila strains.